Granular shape memory ceramic packings. (15th June 2017) - Yu, Hang Z.; Hassani-Gangaraj, Mostafa; Du, Zehui; Gan, Chee Lip; Schuh, Christopher A.
Abstract: Although bulk shape memory ceramics (SMCs) are brittle, in particulate form they exhibit large recoverable strains in both shape memory and superelastic modes. Here, we investigate the fundamentals of mechanically- and thermally-triggered martensitic transformation of granular SMC packings. Specifically, (ZrO2 )1-x -(CeO2 )x is studied in three different composition regimes. In the shape memory regime (below the martensite finish temperature), confined uniaxial compression leads to martensite re-orientation in the granular SMC packing, with the peak intensity of preferred crystallographic orientation increasing with external loading. In the intermediate regime (between austenite start and martensite start temperatures), confined uniaxial compression leads to irreversible martensitic transformation with the transformed volume increasing with external loading. This provides direct evidence of stress-induced martensitic transformation in granular SMCs. In the superelastic regime (above the austenite finish temperature), confined uniaxial compression leads to forward (during loading) and reverse (during unloading) martensitic transformation, manifesting in a large hysteresis loop in each load-unload cycle with remarkably high energy dissipation density. Based on finite element modeling of SMC particles in contact, we explore the martensitic transformation under non-uniform Hertzian stresses, which in turn provides insight on the experimental results. Graphical abstract: Image 1